High-quality bonds: serine acetyltransferase 2 gene revealed by GWAS is associated with grain protein content in spring durum wheat - Ermolaev, Aleksey; Bespalova, Ludmila; Korobkova, Varvara; Yanovsky, Aleksey; Nazarova, Lubov; Kroupina, Aleksandra; Chernook, Anastasia; Mudrova, Aleksandra; Voronezhskaya, Viktoria; Kroupin, Pavel; Karlov, Gennady; Divashuk, Mikhail (Frontiers in Plant Science, 2025)
Grain protein content (GPC) is a critical determinant of durum wheat quality, with cysteine playing a pivotal role in gluten strength. This study aimed to develop genetic markers associated with GPC through a genome-wide association study (GWAS) and validate their utility for breeding programs. A panel of 190 durum wheat accessions was phenotyped for GPC across multiple environments and genotyped using 4927 high-quality SNPs. GWAS identified a significant SNP on chromosome 4B, located in an intergenic region. Through the analysis of linkage disequilibrium decay rate, and functional gene ontology annotation, the serine acetyltransferase 2 gene involved in cysteine biosynthesis was identified as a candidate gene for GPC. A missense mutation (Gly325Ser) in the ninth exon of sat2 was associated with a 1.33% GPC increase in spring durum wheat recombinant inbred lines. Structural analysis indicated that the Gly325Ser mutation alters the SAT2 protein’s C-terminal α-helix, potentially influencing enzyme activity. Additionally, an intronic SNP showed association with multi-year average GPC increase of 0.92% in spring durum wheat. Despite the intronic SNP’s lack of direct amino acid impact, its high phenotypic variance explained (40.23% in spring wheat) suggests regulatory roles in gene expression. Expression profiling of TAsat2 homologous from bread wheat revealed peak transcription during grain filling stages, aligning with grain protein accumulation dynamics. The developed KASP markers demonstrated robust allelic discrimination, offering practical tools for marker-assisted selection. This study provides actionable genetic resources for breeding high-protein spring durum wheat genotypes.